Are we ever too old?: Characteristics and outcome of octogenarians admitted to a medical intensive care unit. Issue 37 (September 2017) - Muessig, Johanna Maria; Masyuk, Maryna; Nia, Amir Movahed; Franz, Marcus; Kabisch, Bjoern; Kelm, Malte; Jung, Christian
Abstract : Abstract: The aging population increases the demand of intensive care unit (ICU) treatments. However, the availability of ICU beds is limited. Thus, ICU admission of octogenarians is considered controversial. The population above 80 years is a very heterogeneous group though, and age alone might not be the best predictor. Aim of this study was to analyze resource consumption and outcome of octogenarians admitted to a medical ICU to identify reliable survival predictors in a senescent society. This retrospective observational study analyzes 930 octogenarians and 5732 younger patients admitted to a medical ICU. Admission diagnosis, APACHE II and SAPS II scores, use of ICU resources, and mortality were recorded. Long-term mortality was analyzed using Kaplan-Meier survival curves and multivariate cox regression analysis. Patients ≥80 years old had higher SAPS II (43 vs 38, P < .001) and APACHE II (23 vs 21, P = .001) scores. Consumption of ICU resources by octogenarians was lower in terms of length of stay, mechanical ventilation, and renal replacement therapy. Among octogenarians, ICU survivors got less mechanical ventilation or renal replacement therapy than nonsurvivors. Intra-ICU mortality in the very old was higher (19% vs 12%, P < .001) and long-term survival was lower (HR 1.76, P < .001). Multivariate cox regression analysis of octogenarians revealed that admission diagnosis of myocardial infarction (HR 1.713, P = .023), age (1.08, P = .002), and SAPS II score (HR 1.02, 95%, P = .01) were independent risk factors, whereas admission diagnoses monitoring post coronary intervention (HR .253, P = .002) and cardiac arrhythmia (HR .534, P = .032) had a substantially reduced mortality risk. Octogenarians show a higher intra-ICU and long-term mortality than younger patients. Still, they show a considerable life expectancy after ICU admission even though they get less invasive care than younger patients. Furthermore, some admission diagnoses like myocardial infarction, cardiac arrhythmia and monitoring post cardiac intervention are much stronger predictors for long-term survival than age or SAPS II score in the very old.